The Effect of 2,4-D (2,4-Dichlorophenoxyacetic Acid) and Kinetin (6-Furfuryl Amino Purine) Concentrations on The Induction of Embryogenic Callus In Porang (Amorphophallus muelleri Blume) In Vitro - Agung, Nadya Rahadianti; Huddi, Darul; Putri, Amalia Nasyira; Resmisari, Ruri Siti (El-Hayah:Jurnal Biologi, 2023)
Porang (Amorphophallus muelleri Blume) belongs to the family Araceae and holds significant potential for cultivation in Indonesia. It contains more than 50% glucomannan in its corms. Porang is commonly commercialized as flour and chips and has found extensive use in the food, cosmetics, chemical, pharmaceutical, and coating industries. Conventional propagation of Porang often takes a long time, approximately 2-3 years, making it unable to meet the demand for Porang seedlings quickly. In vitro propagation using plant growth regulators 2,4-D and kinetin is being explored to induce embryogenic callus, offering a solution for large-scale cultivation of high-quality Porang within a shorter timeframe. This research adopts an experimental approach employing a completely randomized design (CRD) with two factors. The first factor is the auxin 2,4-D (2,4-Dichlorophenoxyacetic acid), and the second factor is the cytokinin kinetin. The optimal concentration for inducing embryogenic callus in Porang is found to be 2,4-D at 1 mg/L and kinetin at 0 mg/L, resulting in intermediate callus with a yellowish-brown color and a wet weight of 2.43 grams.